Six new species of Saussurea (Asteraceae) from eastern Himalaya - Chen, Yousheng (Phytotaxa, 2014)
Six new species of Saussurea (Asteraceae, Cardueae) from eastern Himalaya, namely S. austrotibetica, S. bhutanensis, S. langpoensis, S. lhozhagensis, S. lhunzensis, and S. pagriensis are described and illustrated.